Companion crops upon Eucalyptus urograndis initial development - Délio Braga Marques (Bosque, 2015)
The present work aims at evaluating the initial development of two Eucalyptus urograndis (eucalypt) clones (H017 and H1069) consorted with maize in six plants per meter; soy in eighteen plants per meter; beans in ten plants per meter; and signal-grass, with 0.5 kg m-2 of seeds. The eucalypt planting was upheld in cement vases -70 L of capacity, filled with red oxisol- in the center of the vase. The crops were sown equidistant from the border, in one or two sowing lines. A randomized block design was used, in a 5x2 factorial scheme, using five crops (maize, bean, soy, signal grass and control treatment) in two densities (one and two sowing lines), all with three repetitions. Ninety days after planting, eucalypt height, diameter, foliar area, dry matter of leaves and stem and crops aerial parts dry matter were evaluated. Consort crops negatively affected the initial development of both clones, especially in the density of two sowing lines. Bean and soy were the least harmful crops and maize and signal-grass were the most harmful crops.